2019
DOI: 10.1093/treephys/tpz063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the developmental dynamics of the elongation of a bamboo internode during the fast growth stage

Abstract: Previous studies on the fast growth of bamboo shoots mainly focused on the entire culm. No work about the fast elongation of a single internode, which is the basic unit for the fast growth of bamboo shoots, has been reported so far according to our knowledge. In this study, we have systematically investigated the regulating mechanisms underlying the fast growth of a single bamboo internode of Bambusa multiplex (Lour.) Raeusch. ex Schult. We discovered that the growth of the internode displays a logistic patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 32 publications
8
61
0
Order By: Relevance
“…The cell expansion was mainly caused by the accumulation of soluble sugars and water influx. Wei et al (2019) reported that sugar plays an important role in promoting bamboo internode elongation. A similar conclusion was also reported by Wang et al (2020), stating that the starch-and sucrose-metabolizing enzymes correlated well with the bamboo internode elongation.…”
Section: Sucrose Transport and Metabolism In Bending Internodesmentioning
confidence: 99%
“…The cell expansion was mainly caused by the accumulation of soluble sugars and water influx. Wei et al (2019) reported that sugar plays an important role in promoting bamboo internode elongation. A similar conclusion was also reported by Wang et al (2020), stating that the starch-and sucrose-metabolizing enzymes correlated well with the bamboo internode elongation.…”
Section: Sucrose Transport and Metabolism In Bending Internodesmentioning
confidence: 99%
“…Moso bamboo (Phyllostachys edulis) generates nearly 5 billion US dollars annually in economic value. It is the most important non-timber product used for commercial purposes in East Asia due to its fast growth rate [1,2]. During Moso bamboo shoot growth, the height increase was created by simultaneous cell division and cell elongation.…”
Section: Introductionmentioning
confidence: 99%
“…It lives for about 60 or more years and is widely adapted and amenable to different cultivation systems from agroforestry and monoculture gardens. Being one of the fastest‐growing bamboos (Wei et al., 2018), moso bamboo has a unique rhizome‐dependent proliferation system (Li, Li, Lu, & Chen, 2019; Tao, Fu, & Zhou, 2018; Wei et al., 2019) that runs radially from the mother plant. The rhizomes are thick and segmented and remain underground at shallow depths of about 50 cm.…”
Section: Introductionmentioning
confidence: 99%